Faktor-Faktor yang Mempengaruhi Keputusan Nasabah Memilih Produk Deposito Mudharabah pada PT.Bank Sumut Syariah Kantor Cabang Pembantu Marelan Raya - Exgi Handayani; Muhammad Ridwan (Maslahah : Jurnal Manajemen dan Ekonomi Syariah, 2025)
This study aims to determine the factors that influence customer decisions in choosing Mudharabah deposit products at PT Bank Sumut Marelan Raya Branch Office. This study uses variables of Service, Location, Religiosity that influence Mudharabah Deposit Customer Decisions. This research method uses quantitative research using data collection methods, namely questionnaires or questionnaires, while the data analysis technique used is the multiple regression analysis method. The population in this study were customers at PT Bank Sumut Marelan Raya Branch Office totaling 139 respondents from these respondents, the researcher only took a sample of 103 respondents. The data that has been obtained is then processed using the SPSS Version 25 application. Data processing and analysis techniques are, instrument testing, classical assumption testing, multiple regression analysis and hypothesis testing. From the results of simultaneous hypothesis testing, the Fcount value (85.042)> Ftable (3.09) was obtained, so it can be concluded that service, location and religiosity simultaneously have a significant effect on customer decisions. In addition, from the results of the determination test, it is known that the determination coefficient value in the Adjusted R Square column is 0.720, meaning that the variables Service, Location and Religiosity have an influence of 72.0% on the Customer Decision variable. While 28.0% is influenced by other variables not explained in this study. For the Service variable, the partial t-count value (2.572)> t-table (1.984) is obtained, meaning that the Service variable partially has a significant effect on Customer Decisions. The Location variable partially has a t-count value (3.090)> t-table (1.984), meaning that the Location variable partially has a significant effect on Customer Decisions. The Religiosity variable partially has a t-count value (4.842)> t-table (1.984), meaning that the Religiosity variable partially has a significant effect on Customer Decisions. The results of this study indicate that the variables of Service, Location and Religiosity have an effect on Customer Decisions Using Mudharabah Deposit Products at PT Bank Sumut Marelan Raya Branch Office